2023
DOI: 10.21203/rs.3.rs-3075503/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of dyslipidemia with lumbar disc herniation: A case-control study

Abstract: Purpose: The purpose of this study was to investigate the relationship between dyslipidemia and lumbar disc herniation (LDH). Methods: A total of 269 patients with LDH and 269 patients with lumbar vertebral fracture (LVF) were enrolled in this study. The total cholesterol level (TC), Low-density lipoprotein-cholesterol level (LDL-C), triglyceride level (TG), High-density lipoprotein-cholesterol level (HDL-C), nonHDL-C, ApoB level, ApoB A1 level and arteriosclerosis index (AI) were measured.The 269 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…A case-control study of 269 patients found an increased risk of intervertebral disc degeneration in the setting of dyslipidemia with high TG (OR, 1.753; 95% CI, 1.151, 2.699; p = 0.009), high LDL (OR, 1.952; 95% CI, 1.530, 2.490; p < 0.001), or high total cholesterol (OR, 3.580; 95% CI, 2.182, 55.876; p < 0.001). Disc degeneration was associated with a significantly higher incidence of lumbar disc herniation, and consequently CLBP [ 25 ]. Our study also confirmed the association between LBP and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case-control study of 269 patients found an increased risk of intervertebral disc degeneration in the setting of dyslipidemia with high TG (OR, 1.753; 95% CI, 1.151, 2.699; p = 0.009), high LDL (OR, 1.952; 95% CI, 1.530, 2.490; p < 0.001), or high total cholesterol (OR, 3.580; 95% CI, 2.182, 55.876; p < 0.001). Disc degeneration was associated with a significantly higher incidence of lumbar disc herniation, and consequently CLBP [ 25 ]. Our study also confirmed the association between LBP and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found a meaningful association between diabetes and CLBP [ 9 , 17 , 18 , 19 ], whereas others have reported no relationship [ 20 , 21 ]. Similarly, some studies have suggested a positive relationship between dyslipidemia and CLBP [ 10 , 22 , 23 , 24 , 25 ], whereas others have found no association between them [ 23 , 26 , 27 ]. Based on the results of these published studies, the association between CLBP and chronic diseases is still inconsistent.…”
Section: Introductionmentioning
confidence: 99%